Comparison of total laparoscopic hysterectomy and laparoscopic assisted vaginal hysterectomy – a 2-year retrospective study - Mani, Kanmani; Govindarajan, Mirudhubashini; Selvaraj, Vishranthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy is one of the most commonly performed major surgeries. Recently, increasing number of minimally invasive approaches, such as TLH and LAVH has been applied. People undergoing laparoscopic hysterectomy experience shorter hospitalization, a smaller wound, more rapid recovery, and shorter absence from work compared to patients undergoing abdominal hysterectomy. The objective of present study is to compare the surgical short term results between Laparoscopic assisted vaginal hysterectomy (LAVH) and Total laparoscopic hysterectomy (TLH) in our centre in two years. Methods: This was a retrospective study of 93 women who underwent LAVH and 55 women who underwent TLH. The statistical analysis is done by using Students t-test, Chi-square test, and Mann-Whitney test appropriately. Results: There were no differences between the two groups with respect to age, BMI, Indication of surgery, Uterine size, Previous pelvic surgery, average blood loss and hemoglobin change (P=0.4). The duration of surgery was longer in TLH (124 min vs. 76.9 min) and is found to be extremely significant (P=0.0001). There was significant statistical difference in respect to hospital stay (P=0.0076). There was no significant statistical difference in various complication rates (P=0.22). Conclusions: Both TLH and LAVH are safe methods in performing hysterectomy, but LAVH has advantages over TLH with reduced operating time and less hospital stay even for the patients with history of previous pelvic surgery.